Demographic and clinical characteristic of Cerebral Palsy Among Children in Diyala Province – Iraq - Al-Azzawi , Dawood Salman Hameed (Diyala Journal of Medicine, 2019)
Background: Cerebral palsy (CP) is defined as non-progressive disorder of movement and posture due to brain insult or injury occurring in the period of early brain growth (generally under three years of age). Objectives: This is a descriptive study of the demographic and clinical characteristics of cerebral palsy in Diyala province – Iraq is to put the light on this upsetting neurological disorder. Patients and Methods: This study is carried out among children who were referred from the primary health care centers to the reference consultation clinic at Al-battool Maternity and Children teaching hospital in Baquba, the center of Diyala governorate from the first of May 2008 till 30th of April 2011. The following data were studied, the presenting compliant, patients age and sex distribution, mode of delivery, age of presentation, number of full-term and pre-term, the condition at birth and birth asphyxia, types of CP and associated medical abnormalities. Results: The total number of patients were 82, males were affected more than females, the ratio is (1.4:1) (male 48 =58.5% and female34=41.5%).The most common first presenting complaints were the delayed milestones (50%). Most of the patient presented between the age of (7-12) months (48.8%). Spastic CP was the most common type (57.3%), among the other types of spastic CP are spastic quadriplegia (45.1%). Most of the patients are product of vaginal delivery (61%). Most of the patients came to parents who had consanguineous marriage (58%). Conclusions: The study explain that the high prevalence of spastic quadriplegia which is the most common type of CP encountered in the clinical practice is due to the high prevalence of birth asphyxia. Recommendations: 1- To prevent the treatable causes of CP e.g. asphyxia and kernicterus, through initiation of centers for early detection of childhood disability. 2- Establish special centers to look after CP patients specially those need orthopedic surgery and physiotherapy and so on.